An implementation of an electronic tongue system based on a multi-sensor potentiometric readout circuit with embedded calibration and temperature compensation. (November 2016) - Chung, Wen-Yaw; Silverio, Angelito A.; Tsai, Vincent F.S.; Cheng, Cheanyeh; Chang, Shu-Yu; Ming-Ying, Zhou; Kao, Chi-Ying; Chen, Si-Yuan; Pijanowska, Dorota G.; Rustia, Dan; Lo, Yi-Wen
Abstract: We present an electronic tongue system composed of an analog front-end (AFE) with embedded calibration and temperature compensation for interfacing with an array of Ion-Sensitive FETs (ISFETs) or Enzyme – Extended Gate FETs (EEGFET). The AFE consists of a floating bridge type constant voltage constant current (CVCC) structure, and transmission gates as sensor enable. It also includes a temperature readout circuit and an instrumentation amplifier for temperature compensation. The calibration algorithm is synthesized into a Field Programmable Gate Array (FPGA) and implemented onto an Application Specific Integrated Circuit (ASIC). The system shall be used to measure the pH and the concentration of calcium ions in a solution alongside a conductometric sensor system. The ISFETs used are from ITE-Poland and shall be utilized to measure pH; meanwhile, to measure the Ca 2+ concentration, EEGFETs with calcium ionophore on polyvinyl chloride (PVC) on SnO2 /ITO/Glass thin film have been fabricated. The performance of the system using pH buffer solutions of pH 4–10, and CaCl2 buffer concentrations of 0.001–1 M has been verified. The sensors and the AFE readout exhibited a Nernstian response (~50 mV/pH) with a very stable output having a relative standard deviation of just ~−0.4%, and a Ca 2+ sensitivity of 25.02 mV/pCa, with a drift of −6.82 mV/M-s. An on-chip version of the AFE using TSMC 0.35 µm CMOS 2P4M Technology is also presented as well as the ASIC implemented on TSMC 0.18 µm CMOS 1P6M technology.